2015
DOI: 10.1136/bmjopen-2014-007518
|View full text |Cite
|
Sign up to set email alerts
|

Professionalism dilemmas, moral distress and the healthcare student: insights from two online UK-wide questionnaire studies

Abstract: ObjectiveTo understand the prevalence of healthcare students’ witnessing or participating in something that they think unethical (professionalism dilemmas) during workplace learning and examine whether differences exist in moral distress intensity resulting from these experiences according to gender and the frequency of occurrence.DesignTwo cross-sectional online questionnaires of UK medical (study 1) and nursing, dentistry, physiotherapy and pharmacy students (study 2) concerning professionalism dilemmas and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
111
3
4

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 73 publications
7
111
3
4
Order By: Relevance
“…Furthermore, it would raise ethical awareness, which is necessary for resolving the various ethical issues that nurses may encounter in the clinical setting. [4,5] The ethical education makes nursing students ready to handle the ethical conflicts that they may encounter during their clinical practice. [6] Therefore, it is necessary for nursing education to focus on developing an understanding of desirable nursing behaviors, which will improve students' ability to cope with different medical ethical problems that they might encounter when working as nurses in the future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it would raise ethical awareness, which is necessary for resolving the various ethical issues that nurses may encounter in the clinical setting. [4,5] The ethical education makes nursing students ready to handle the ethical conflicts that they may encounter during their clinical practice. [6] Therefore, it is necessary for nursing education to focus on developing an understanding of desirable nursing behaviors, which will improve students' ability to cope with different medical ethical problems that they might encounter when working as nurses in the future.…”
Section: Introductionmentioning
confidence: 99%
“…[13] It has been suggested that education on the code of ethics might help to establish the identity of professional nursing behaviors and promote professional development. [4] In addition, it has been argued that educational interventions or experiential stimulation should be implemented since the initial stage of theoretical education and clinical practice, to help students to recognize the code of nursing ethics and promote the establishment of professional values. [14,15] Thus, it has been suggested that nursing students could learn to develop desirable relationships with other nurses, nursing clients as humans, and various cooperators as a result of ethics education, as well as to understand their professional obligations as experts and to establish desirable professional values.…”
Section: Introductionmentioning
confidence: 99%
“…With their subordinate position in the health care hierarchy, medical students experience moral distress in response to many different situations, including witnessing or participating in provision of futile or nonindicated care or disrespectful behavior [7,8]. Students might remain silent because they fear that voicing concerns could offend superiors and negatively impact their evaluations, as in Lauren's case.…”
Section: Commentarymentioning
confidence: 99%
“…Such dilemmas arise in situations in which students witness and/or are asked to participate in professional lapses such as patient safety, dignity, and consent breaches [5] rather than in ethical dilemma situationstypically encountered by health care professionals-in which decisions need to be made about life-sustaining treatment or the patient's best interest is in question. For example, a professionalism dilemma can be experienced by medical students when they witness senior clinicians jeopardizing patient safety through poor hygiene practices or disrespecting patient dignity through physically exposing patients' bodies for longer than necessary [2,[6][7][8][9]. Furthermore, medical students' seniors frequently request that they undertake activities during workplace learning that violate ethical principles, including examinations (sometimes intimate examinations) without valid patient consent and covering up mistakes, both of which potentially result in patient harm [2, 6-8, 10, 11].…”
Section: Professionalism Dilemmasmentioning
confidence: 99%
“…Indeed, a systematic review of research examining psychological distress in medical students suggests they suffer a high degree of depression and anxiety and greater psychological distress than the general population [1]. In this article, we consider medical students' distress, focusing on moral distress, i.e., emotional distress arising from the dissonance between one's ethical/moral beliefs and one's behavior, which occurs when one's actions are perceived as being limited by institutional constraints or unequal power relations [2][3][4]. By highlighting the concepts of professionalism dilemmas and moral decision making, we examine various types of dilemmas encountered by students, how they respond to those dilemmas, and any resultant moral distress they experience.…”
mentioning
confidence: 99%